Application of in situ Solid-Phase Microextraction on Mediterranean Sponges for Untargeted Exometabolome Screening and Environmental Monitoring - Bojko, Barbara; Onat, Bora; Boyaci, Ezel; Psillakis, Eleftheria; Dailianis, Thanos; Pawliszyn, Janusz (Frontiers in Marine Science, 2019)
In marine ecosystems, sponges are ubiquitous sessile organisms that contain a wide range of specialized metabolites. These metabolites point to a diverse range of biochemical pathways. Some of these compounds are biomarkers that indicate the presence of bacteria that form symbiotic relationships with a host sponge (microsymbionts). Sponges hold considerable promise as bioindicators for seawater quality monitoring, as they are exposed to, and accumulate, significant levels of anthropogenic contamination in coastal areas. Solid-phase microextraction (SPME) is a low-invasive and non-exhaustive technique that combines sampling and extraction into a single step and offers the added benefit of biocompatible extraction phases. We used different types of SPME devices to extract exometabolites from sponges (genus: Sarcotragus) in situ. Following extraction, the samples were analyzed via GC- and LC-MS in order to verify the presence of compounds associated with quorum sensing, as well as to examine the metabolism of organic pollutants, such as monocyclic aromatic hydrocarbons (MAHs), polycyclic aromatic hydrocarbons (PAHs), pesticides, and other bioactive compounds in an untargeted format. As the results demonstrate, when the extracted metabolites are compared with the background controls, SPME offers a non-exhaustive approach that can be used in the field to discover novel metabolites deriving from complex holobionts such as marine sponges.